2008
DOI: 10.1186/1475-2875-7-44
|View full text |Cite
|
Sign up to set email alerts
|

Use of antenatal care, maternity services, intermittent presumptive treatment and insecticide treated bed nets by pregnant women in Luwero district, Uganda

Abstract: Background: To reduce the intolerable burden of malaria in pregnancy, the Ministry of Health in Uganda improved the antenatal care package by including a strong commitment to increase distribution of insecticide-treated nets (ITNs) and introduction of intermittent preventive treatment with sulphadoxine-pyrimethamine for pregnant women (IPTp-SP) as a national policy in 2000. This study assessed uptake of both ITNs and IPTp-SP by pregnant women as well as antenatal and maternity care use with the aim of optimizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 18 publications
9
42
2
Order By: Relevance
“…This finding is similar to what was found in Ibadan by Dairo et al 16 , in the Sagamu study 13 and in an Uganda study by Kiwuwa et al 17 where utilization of ANC services was found to be 76.8%, 84.6% and 94.4% respectively. This is in contrast to what was found in Kano where only 24.7% of the women had visited a clinic or facility for ANC at least once during their most recent pregnancy.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to what was found in Ibadan by Dairo et al 16 , in the Sagamu study 13 and in an Uganda study by Kiwuwa et al 17 where utilization of ANC services was found to be 76.8%, 84.6% and 94.4% respectively. This is in contrast to what was found in Kano where only 24.7% of the women had visited a clinic or facility for ANC at least once during their most recent pregnancy.…”
Section: Discussionsupporting
confidence: 80%
“…In a study done in Entebbe, a Semi urban locality of Uganda Tann et al [21] found that only 16% of women have their first visit in the first trimester. In another study in rural Uganda this time, Kiwuwa and Mufubenga [22] found that 57.7% of women booked for ANC in the first trimester. The finding of our study was similar to those of Ali et al [23] in Kassala, Eastern Sudan where 31% of women booked for ANC in the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with most previous studies in African women which show that the average timing was usually in the second trimester. 8,9,10,14 It was interesting to note that as much as about three quarter of the women felt that the first three months of pregnancy was the best time to register for antenatal care. This knowledge most likely came from health education programs during previous pregnancies, hospitals or the news media but the booking pattern suggests that most of the women were not convinced that there was any gain in registering for antenatal care early or had constraints hence the discordance between knowledge and practice in most of them.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported from other countries in sub-Saharan Africa suggesting that this is a wide spread practice. 10,11 While studies from most developed countries have established that socially disadvantaged women such as teenagers ,unmarried women and women with lower level of education and lower socioeconomic class are more likely to book late for antenatal care, studies from sub-Saharan Africa suggest that these may not be the major determinants in Afri-can women. 12,13 Previous studies from Nigeria are inconclusive.…”
Section: Introductionmentioning
confidence: 99%